Altered Relation Between Lipopolysaccharide‐Induced Inflammatory Response and Excitotoxicity in Rat Organotypic Hippocampal Slice Cultures During Ethanol Withdrawal. (6th April 2015) - Lutz, Joseph A.; Carter, Megan; Fields, Logan; Barron, Susan; Littleton, John M.
<x xml:space="preserve">Abstract</x> Background Ethanol (EtOH) causes neurotoxicity by several mechanisms including excitotoxicity and neuroinflammation, but little is known about the interaction between these mechanisms. Because neuroinflammation is known to enhance excitotoxicity, we hypothesized that neuroinflammation contributes to the enhanced excitotoxicity, which is associated with EtOH withdrawal (EWD). The aim of this study was to evaluate the lipopolysaccharide (LPS)‐induced inflammatory response of cultured hippocampal tissue during EWD and its effects on the enhanced N‐methyl‐d‐aspartate (NMDA) receptor‐mediated excitotoxicity, which occurs at this time. Methods Using a neonatal organotypic hippocampal slice culture (OHSC) model, we assessed the effects of NMDA and LPS (separately or combined) during EWD after 10 days of EtOH exposure. Neurotoxicity was assessed using propidium iodide uptake, and the inflammatory response was evaluated by measuring the release of tumor necrosis factor (TNF)‐alpha (quantified by enzyme‐linked immunosorbent assay) and nitric oxide (NO; quantified by the Griess reaction) into culture media. Furthermore, we explored the potential role of the microglial cell type using immortalized BV2 microglia treated with EtOH for 10 days and challenged with LPS during EWD. Results As predicted, NMDA‐induced toxicity was potentiated by LPS under control conditions. However, during EWD, the reverse was observed and LPS inhibited peak NMDA‐induced toxicity. Additionally, LPS‐induced release of TNF‐alpha and NO during EWD was reduced compared to control conditions. In BV2 microglia, following EtOH exposure, LPS‐induced release of NO was reduced, whereas TNF‐alpha release was potentiated. Conclusions During EWD following chronic EtOH exposure, OHSC exhibited a desensitized inflammatory response to LPS and the effects of LPS on NMDA toxicity were reversed. This might be explained by a change in microglia to an anti‐inflammatory and neuroprotective phenotype. In support, studies on BV2 microglia indicate that EtOH exposure and EWD do alter the response of these cells to LPS, but this cannot fully explain the changes observed in the OHSC. The data suggest that neuroinflammation and excitotoxicity do interact during EWD. However, the interaction is not as simple as we originally proposed. This in turn illustrates the need to assess the extent, importance, and relation of these mechanisms in models of EtOH exposure producing neurotoxicity.